United Nations Resource Management System - United Nations Economic Commission for Europe (United Nations, 2023)
The multifaceted requirements of sustainable development depend on optimal and responsible production and use of natural resources. The United Nations Resource Management System (UNRMS) provides the framework for integrated and sustainable management of natural resources to promote good social, environmental and economic outcomes in alignment with the 2030 Agenda for Sustainable Development. UNRMS is based on the United Nations Framework Classification of Resources (UNFC) and provides a sustainable transition pathway for producing, using and reusing natural resources to become engines of sustainable development.